Structural, optical and electrical properties of F-doped ZnO nanorod semiconductor thin films deposited by sol-gel process - Ilican, Saliha; Caglar, Yasemin; Caglar, Mujdat; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2008)
Structural, optical and electrical properties of fluorine-doped ZnO nanostructure semiconductor thin films prepared by sol-gel spin coating method have been investigated. The thin films have polycrystalline structure with a preferential growth along the ZnO (0 0 2) plane. The grain size for the films was found to be in the range of 24-35 nm. Scanning electron microscopy (SEM) images clearly revealed that the 10% F-doped ZnO film was composed of nanorods. Transmittance spectra of the films indicate that the films have high transparency. The optical band gap and Urbach energy of the F-doped ZnO films vary with fluorine doping. The refractive index dispersion curve of 20% F-doped ZnO film obeys the single-oscillator model. The dispersion parameters, E-o and E-d were found to be 6.104 and 12.045 eV, respectively. For 10% F-doped ZnO film, temperature-dependent conductivity studies revealed that the conduction mechanism is changed from the thermally activated conductivity to the grain boundary scattering with increase in temperature. (C) 2008 Elsevier B. V. All rights reserved.
Keywords: Fluorine-doped ZnO; Sol-gel spin coating; Single-oscillator model; Electrical properties